2015
DOI: 10.14814/phy2.12425
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds of skin sensitivity are partially influenced by mechanical properties of the skin on the foot sole

Abstract: Across the foot sole, there are vibration and monofilament sensory differences despite an alleged even distribution of cutaneous afferents. Mechanical property differences across foot sole sites have been proposed to account for these differences. Vibration (VPT; 3 Hz, 40 Hz, 250 Hz), and monofilament (MF) perception threshold measurements were compared with skin hardness, epidermal thickness, and stretch response across five foot sole locations in young healthy adults (n = 22). Perceptual thresholds were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
66
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 55 publications
11
66
2
1
Order By: Relevance
“…The stimulus was above perceptual threshold for all participants, in agreement with established vibrotactile thresholds (Bolanowski et al, 1988; Strzalkowski et al, 2015b; Mildren et al, 2016). High frequency stimuli (above ~30 Hz) has been shown to activate predominantly fast adapting cutaneous afferents, however, at the high amplitude used in the present study, afferent firing is expected across all four afferent classes (Johansson et al, 1982).…”
Section: Discussionsupporting
confidence: 87%
“…The stimulus was above perceptual threshold for all participants, in agreement with established vibrotactile thresholds (Bolanowski et al, 1988; Strzalkowski et al, 2015b; Mildren et al, 2016). High frequency stimuli (above ~30 Hz) has been shown to activate predominantly fast adapting cutaneous afferents, however, at the high amplitude used in the present study, afferent firing is expected across all four afferent classes (Johansson et al, 1982).…”
Section: Discussionsupporting
confidence: 87%
“…A previous study showed that the thickest and hardest plantar region was the heel while the fifth metatarsal, first toe and LM have intermediate hardness and thickness following heel. The same study indicated that plantar thickness and hardness had a positive correlation with plantar sensitivity . The results of the present study can be explained by this correlation of plantar thickness and hardness with plantar sensitivity.…”
Section: Discussionsupporting
confidence: 82%
“…Ageing usually causes disorders in the somatosensory system. Plantar cutaneous feedback is reduced by factors such as changes in the peripheral nervous system and breakdown of mechanical properties of the skin in the older people . Tactile sensitivity contributes to maintain the balance by providing feedback from the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increased skin hardness was only associated to an elevated vibration threshold at the 25 Hz vibration frequency while the k coefficient of the Stevens power function was affected at both the 25 and 150 Hz frequencies. Examining the data reported by Strzalkowski et al [10], who reported a discrete relationship between the foot sole skin hardness and the vibration sensitivity, revealed first, that the skin hardness of the five foot sole locations tested, mostly that of the 5 th metatarsal head, was lower than that measured in our subjects and also that the difference between the skin hardness was minor, varying only from 33 to 46 Shore between the locations. This could explain the absence of any significant correlation between the perceptual vibration threshold and the skin hardness.…”
Section: Discussionsupporting
confidence: 65%
“…In their princeps study, Strzalkowski et al [10] have explored the vibration threshold of the medial arch of the foot sole and the heel. They only noted a trend of elevated sensory threshold at harder and thicker sites and they did not find any correlation between skin hardness and the vibration perceptual thresholds, concluding that skin hardness and epidermal thickness appeared to have a negligible influence on the vibration sensitivity.…”
Section: Introductionmentioning
confidence: 99%